The relationship between the air temperature change daily, farmer behavior, and diversity pollinating insects in the district of Bumijawa Tegal Central Java - Yuliani, Dwi (Jurnal Ilmiah BioSmart (JIBS), 2021)
Global warming has threatened Indonesian’s agricultural sector and set the sector vulnerable to climate change. The changes affect the daily air temperature changes, farmer behavior, and the diversity of insect pollinators. The study aims to determine the daily changes in air temperature, farmer behavior, and diversity of pollinating insects in the Bumijawa, Tegal, Central Java; and to analyze the relationship between daily air temperature changes, farmer behavior, and insect pollinators diversity. The research employed survey methods. Samples for the daily air temperature measurement were taken purposeviley. The diversity of insect pollinators on the three farming type and respondens were selected radmonly with total respondent 99. The results showed that the average daily air temperature in chili farms is higher than that in tomato and strawberry farm; farmers have a good knowledge about the environmental degradation of agriculture land, good attitude and awareness in maintaining and improving the quality of agriculture, but they have negative behaviour in the use of excessive doses of fertilizer. Species richness of insect pollinators in tomato farm is higher than that in chili and strawberry farm. A good knowledge, good attitude, and bad behaviour are closely related to the daily air temperature and insect pollinators.